2010
DOI: 10.21123/bsj.7.1.168-173
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thickness on Some Optical Properties of Sb2S3 Thin Films Prepared by Chemical Bath Deposition

Abstract: Sb2S3 thin films have been prepared by chemical bath deposition on a glas sub Absorbance and transmittance spectra were recorded in the wavelength range (30-900) nm. The effects of thickness on absorption coefficient, reflectance, refractive index, extinction coefficient, real and imaginary parts of dielectric constant were estimated. It was found that the reflectivity, absorption coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It found that the reflection coefficient, adsorption coefficient, real part of the dielectric permittivity, and refractive index decrease with increasing film thickness, while the imaginary part of the dielectric permittivity increases. [79].…”
Section: Chemical Deposition Methodsmentioning
confidence: 99%
“…It found that the reflection coefficient, adsorption coefficient, real part of the dielectric permittivity, and refractive index decrease with increasing film thickness, while the imaginary part of the dielectric permittivity increases. [79].…”
Section: Chemical Deposition Methodsmentioning
confidence: 99%